Gaultheria shallon can be controlled by the herbicides picloram, triclopyr or glyphosate if they are applied at the correct time of year. Issue 6 (November 2018) - Willoughby, Ian; Forster, Jack; Stokes, Victoria
Abstract Salal (Gaultheria shallon ) is a vigorous evergreen perennial shrub that is native to the west coast of North America, where it can reduce overstorey growth rates and negatively impact regeneration. Since its introduction into the UK almost a century ago it has become an increasing problem in many woodlands, where it completely shades out other understorey vegetation including young trees, preventing forest regeneration. Climate change is likely to favour its future spread in the UK, and in other regions which currently have a similar climate such as Ireland and northwest Europe. Non chemical management is only practical on a small scale, and to date efforts to control this invasive weed with herbicides have been largely ineffective. In our work we found that a single application of 2.69 kg active ingredient (a.i.) ha−1 picloram [as 11.2 l ha−1 Tordon 22 K (240 g l−1 picloram)] diluted in water plus the adjuvant Mixture B NF at 2% of final spray volume, applied between spring and midsummer, killed all treated plants within two growing seasons. Treatment with 3.84 kg a.i. ha−1 triclopyr [as 8 l ha−1 Timbrel (480 g l−1 triclopyr)] diluted in water plus Mixture B NF at 2% of final spray volume, sprayed initially when flower buds are swelling or flushed but vegetative buds are largely dormant (late April in southern Britain), with a repeat application made 4–8 weeks later, was also very effective. If triclopyr or picloram cannot be used, we also found that glyphosate can provide some control, but follow up treatment will be required. In addition, silvicultural practices such as the high density planting of heavily shade bearing species should be adopted to discourage subsequent reinfestation of cleared areas.